The Hidden Dividends of Microservices. - KILLALEA, TOM (Communications of the ACM, 2016)
The article discusses benefits of microservices in relation to distributed systems that use APIs (application program interfaces). Topics include the notion of permissionless innovation as opposed to gatekeepers blocking integration, the needs to enable failure using microservices, and the relation of service-level agreements (SLAs) to trust.